Class in the Composition Classroom : Pedagogy and the Working Class - Carter, Genesea M. (Genesea Mackenzie), 1979-; Thelin, William H. (Book collections on Project MUSE., 2017)
"What college writing instructors should know about working-class students--their backgrounds, experiences, identities, learning styles, and skills--in order to support them in the classroom, across campus, and beyond. Contributors explore the nuanced and complex meaning of "working class" and the values these writers bring"--Provided by publisher